2018
DOI: 10.4103/jnrp.jnrp_93_17
|View full text |Cite
|
Sign up to set email alerts
|

Acute Febrile Encephalopathy in Children: A Prospective Study of Clinical Features, Etiology, Mortality, and Risk Factors from Western India

Abstract: Introduction:Acute febrile encephalopathy (AFE) in children is a medical emergency and could be a manifestation of many systemic and central nervous system pathologies. The clinical features of AFE are nonspecific and etiological spectrum variable depending on the studied population.Materials and Methods:A prospective, observational study was carried out including children aged between 1 month and 12 years with AFE admitted to the Pediatric Intensive Care Unit of a tertiary care hospital in Western India. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…In contrast to our study, they found maximum sequelae in bacterial meningoencephalitis (61.7%) followed by viral encephalitis (31.9%). Our study corroborates with the study by Kirti Gupta et al (2) that showed highest mortality in the group with inconclusive aetiology (50%) followed by viral group (25%) and bacterial meningoencephalitis group (16.6%).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast to our study, they found maximum sequelae in bacterial meningoencephalitis (61.7%) followed by viral encephalitis (31.9%). Our study corroborates with the study by Kirti Gupta et al (2) that showed highest mortality in the group with inconclusive aetiology (50%) followed by viral group (25%) and bacterial meningoencephalitis group (16.6%).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Kirti Gupta et al (2) showed that fever and altered sensorium were present in 100% cases. Seizure was present in 71.1% cases and vomiting in 35.6% cases, which were less than our study.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations